Konsep Pendidikan Karakter Dalam Kitab Bidāyah Al-Hidāyah Karya Imam Al-Ghazali - Rahman, Abdul (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
It is very worrying that the deterioration of character, especially cases of violence, harassment, murder, and drunkenness are occurring. Therefore, to answer this problem, of course you need to take a stand by providing character education to the nation’s children. It is important to examine the concept of character education in the Bidāyah al-Hidāyah book by Imam Al-Ghazali with the aim of this research to determine the concept of character education in the Book of Bidāyah al-Hidāyah by Imam Al-Ghazali. The method used in this study is field research, the results of the character education research are quite comprehensive, namely covering relationships in the context of society, oneself and the relationship with God. There is character education including: religious character, namely obedience to Allah SWT, responsibility, namely forming a personality, healthy lifestyle, namely being good from a physical perspective. Conclusion Character education is an effort made by an educator to form a good personality in a student both in terms of physical and spiritual, mental and spiritual so that a human being is formed who is obedient to God. The suggestions for character education in the book Bidāyah al-Hidāyah should be applied by every individual, especially in the world of education.